La memoria de responsabilidad social empresarial - Echaiz Moreno, Daniel (Revista de Derecho, 2019)
The company develops contemporary converge in a world where corporate governanceand corporate social responsibility as two pillars that guide its action. Thus, the CorporateSocial Responsibility Report shows how the company is committed to sustainabledevelopment of their social environment. It is not sufficient for the preparation andsubmission of the report required by the Corporations Act, but now the market advocatesalso have it. In this paper we present the most important aspects of this new figure thatis gaining ground abroad and deserves to be treated in our country.
Keywords: Sustainability; social responsibility; corporate governance; stakeholders